2001
DOI: 10.1083/jcb.152.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pyk2 to β1-Integrin–Containing Focal Contacts Rescues Fibronectin-Stimulated Signaling and Haptotactic Motility Defects of Focal Adhesion Kinase–Null Cells

Abstract: Focal adhesion kinase–null (FAK−/−) fibroblasts exhibit morphological and motility defects that are reversed by focal adhesion kinase (FAK) reexpression. The FAK-related kinase, proline-rich tyrosine kinase 2 (Pyk2), is expressed in FAK−/− cells, yet it exhibits a perinuclear distribution and does not functionally substitute for FAK. Chimeric Pyk2/FAK proteins were created and expressed in FAK−/− cells to determine the impact of Pyk2 localization to focal contacts. Whereas an FAK/Pyk2 COOH-terminal (CT) domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 62 publications
8
62
1
1
Order By: Relevance
“…It is now well established that the focal adhesion kinase (FAK) tyrosine kinase family plays a crucial role in the signaling pathways implicated during the cellular adherence and migration (42)(43)(44). We first observed that, as demonstrated in freshly isolated human monocytes (45,46) and in THP1 cells (14), the human monocytic MonoMac cells express only the related FAK tyrosine kinase Pyk2 and not p125 FAK (Fig.…”
Section: S-fkn Abrogates the Mcp-1-induced Activation Of Pyk2 In Monomentioning
confidence: 97%
See 1 more Smart Citation
“…It is now well established that the focal adhesion kinase (FAK) tyrosine kinase family plays a crucial role in the signaling pathways implicated during the cellular adherence and migration (42)(43)(44). We first observed that, as demonstrated in freshly isolated human monocytes (45,46) and in THP1 cells (14), the human monocytic MonoMac cells express only the related FAK tyrosine kinase Pyk2 and not p125 FAK (Fig.…”
Section: S-fkn Abrogates the Mcp-1-induced Activation Of Pyk2 In Monomentioning
confidence: 97%
“…Members of the FAK family have been shown to play a key role in the control of the adhesion/migration process (42)(43)(44) and also to intervene in the control of MAPK pathways (47, 49 -51). We found that FAK is not expressed in MonoMac6 cells, whereas Pyk2, which is highly expressed in this cell line, was rapidly stimulated in response to MCP-1, in accord with previous data obtained on THP-1 cells (14) and on freshly isolated monocytes with RANTES (45).…”
Section: Discussionmentioning
confidence: 99%
“…Pyk2, another member of FAK family kinase, is highly expressed in hematopoietic, endothelial, and neuronal cells (Dikic and Schlessinger, 1998;Lev et al, 1995). Although both kinases exhibit structural similarities, their subcellular localization and functions are distinct (Klingbeil et al, 2001).…”
Section: Structure and General Features Of Fak Family Kinasesmentioning
confidence: 99%
“…1). FAK C-terminal domain is called as focal adhesion targeting (FAT) domain which contains binding sites for both paxillin and talin, thereby connects to cellular adhesion sites called focal adhesions (FAs) while the C-terminal domain of Pyk2 does not have talin binding motif and do not normally localize to the FAs (Klingbeil et al, 2001;Lawson et al, 2012). This difference makes Pyk2 subcellular localization more favorable to perinuclear region than FAs.…”
Section: Structure and General Features Of Fak Family Kinasesmentioning
confidence: 99%
“…The beneficial effects for enhanced osteoblast adhesion and migration may result from reorganization of actin cytoskeleton to a certain degree (23). The regulation of cell function by actin cytoskeleton is complex and may also involve integrin-mediated matrix binding and signal pathways (62)(63)(64)(65)(66). In addition, cells need to spread fully during migration (45), and the enhanced ability of osteoblasts to spread would promote cell migration.…”
Section: Journal Of Biological Chemistry 26207mentioning
confidence: 99%